The role of corporate governance in preventing financial statement fraud - Tarkki, Olivia (My University, 2024)
The purpose of this thesis is to examine the connection between corporate governance and financial statement fraud. Corporate governance is a monitoring mechanism for the actions, policies, and decision-making of corporations in increasing shareholder value. Financial statement fraud is defined as an intentional misrepresentation or omission of information. The intent of financial statement fraud is to deceive the users of financial statements for the benefit of the fraudster. The globalization of capital markets and past financial scandals have stressed the need for consistent corporate governance policies. Previous fraud cases have caused reputational damage and financial losses, undermined public confidence in the markets and led to bankruptcies. These consequences have led companies to focus on enhancing their corporate governance. The thesis is conducted as a literature review based on academic articles, research and literature in economics, accounting and finance. In particular, the literature review focuses on the internal corporate governance mechanisms. The aim of the thesis is to identify the optimal characteristics of internal corporate governance mechanisms that can contribute to the prevention of financial statement fraud. With respect to financial statement fraud, this thesis focuses on fraudulent reporting. This thesis uses agency theory to explain the link between corporate governance and financial statement fraud. The literature review shows that corporate governance plays a crucial role in financial statement fraud prevention. Corporate governance enhances managerial control in firms and increases the transparency and reliability of financial reporting. Several studies have shown that the extent of control has an impact on the likelihood of financial statement fraud. Regarding the optimal characteristics of corporate governance mechanisms, the thesis indicates that independence, efficiency and expertise of the members of the institutions in question are of particular importance.

Tämän tutkielman tarkoituksena on tutkia yhteyttä hyvän hallintotavan ja tilinpäätöspetosten välillä. Hyvä hallintotapa on järjestelmä, jolla valvotaan yritysten toimintaa, toimintapolitiikkaa ja päätöksentekoa omistaja-arvon kasvattamisen takaamiseksi. Tilinpäätöspetoksella tarkoitetaan tahallista tietojen vääristämistä tai pois jättämistä tilinpäätöksestä. Sen tarkoituksena on harhaanjohtaa tilinpäätösinformaation käyttäjiä petoksen tekijän hyödyksi. Pääomamarkkinoiden globalisoituminen ja aiemmat finanssiskandaalit ovat korostaneet johdonmukaisten hallintokäytäntöjen tarvetta. Aikaisemmat petostapaukset ovat aiheuttaneet mainehaittoja, taloudellisia tappioita, heikentäneet yleistä luottamusta markkinoihin ja aiheuttaneet konkursseja. Nämä seuraukset ovat saaneet yritykset keskittymään hyvän hallintotavan parantamiseen. Tutkielma on toteutettu kirjallisuuskatsauksena perustuen taloustieteen, laskentatoimen ja rahoituksen akateemisiin artikkeleihin, tutkimuksiin ja kirjallisuuteen. Kirjallisuuskatsaus keskittyy erityisesti hyvän hallintotavan sisäisiin osa-alueisiin ja pyrkii tunnistamaan niiden optimaaliset ominaisuudet, jotka voivat vaikuttaa tilinpäätöspetosten ehkäisemiseen. Tilinpäätöspetosten osalta tämä tutkielma keskittyy painottamaan vilpillistä raportointia. Tutkielmassa käytetään agenttiteoriaa selittämään yhteyttä hyvän hallintotavan ja tilinpäätöspetosten välillä. Kirjallisuuskatsaus osoittaa, että hyvällä hallintotavalla on ratkaiseva merkitys tilinpäätöspetosten ehkäisemisessä. Hyvä hallintotapa tehostaa johtajien valvontaa yrityksissä sekä lisää tilinpäätösraportoinnin avoimuutta ja luotettavuutta. Useiden tutkimusten mukaan valvonnan laajuudella on vaikutus tilinpäätöspetosten todennäköisyyteen. Hyvän hallintotavan osa-alueiden optimaalisten ominaisuuksien osalta tutkielma korostaa erityisesti riippumattomuuden, tehokkuuden sekä toimielinten jäsenten asiantuntemuksen tärkeyttä.
Keywords: corporate governance, financial statement fraud, fraudulent reporting